Risk Factors of Brain Metastasis and Prognosis in HER2-Positive Breast Cancer: A Single-Institution Retrospective Analysis from China - Cai, Shuang-Long; Wang, Zhi-Hong; Chen, Xiao-Geng; Han, Lei; Gong, Guo-Xian; Chen, Yan-Ping; Lin, Xiu-Quan; Ma, Tao; Chen, Hong-Dan (Frontiers in Oncology, 2022)
Background Brain metastasis (BM) frequently occurs in HER2-positive breast cancer (BC) patients, but the risk factors of BM in this type of patients are still unknown. Our study aims to assess the risk factors of BM and prognostic analysis in HER2-positive BC patients. Methods Univariate analysis used t-test, chi-square test, and Fisher’s exact test to find out the risk factors for BM, and multivariable analysis was done with stepwise logistic regression analysis. Prognostic data analysis was estimated by the Kaplan–Meier method. Results A total of 228 HER2-positive BC patients were included, of whom 214 patients were postoperative metastatic patients and 14 patients were de novo stage IV patients. Through comparing the stratified variables between 51 postoperative metastatic patients with BM and 163 postoperative metastatic patients without BM, the multivariate analysis showed that age ≤40 years (OR 2.321, 95% CI: 1.089 to 4.948) and first metastatic site with lung metastasis (OR 2.168, 95% CI: 1.099 to 4.274) were independent risk factors for BM in HER2-positive BC patients. Prognostic data of all 65 HER2-positive BC patients with BM showed that the time from the diagnosis of BC to the development of breast cancer brain metastasis (BCBM) was 36.3 months (95% CI: 30.0 to 42.1 months). The time from the diagnosis of first recurrence and metastasis stage to the diagnosis of BCBM was 11.35 months (95% CI: 7.1 to 18.4 months). The time from the diagnosis of BCBM to the time of follow-up was 24.1 months (95% CI: 13.9 to 37.5 months). Up until the time of follow-up data, a total of 38 patients had died, and the time from the diagnosis of BM of these 38 patients to death was 11.0 months (95% CI: 9.0 to 20.4 months). Conclusion The prognosis of HER2-positive BC patients with BM was poor due to the lack of effective treatments for BM. Age ≤40 years and first metastatic site with lung metastasis were the independent risk factors for BM in HER2-positive BC patients. Future research about pre-emptive medical interventions may help to improve the prognosis of HER2-positive BC patients with high risk to develop BM.